The Fiskenæsset Complex, West Greenland. Part II. General Mineral Chemistry from Qeqertarssuatsiaq. - Windley, B. F.; Smith, J. V. (Meddelelser om Grønland, 1974)
Electron microprobe analyses of 10 metamorphic mineral phases are given for rocks arranged in stratigraphic order through the Fiskenæsset "intrusion": 2 garnets, 11 olivines, 16 orthopyroxenes, 9 clinopyroxenes, 38 hornblendes, 8 phlogopites, 24 plagioclases, 6 spinels (pleonaste), 7 chromites and 7 magnetites. The element contents in minerals plotted with respect to zonal position in the intrusion and the inter-element distributions within minerals and between coexisting minerals suggest that the original igneous crystallization pattern of this gravity-differentiated, layered body has been only partly modified by metamorphic re-equilibration under hornblende granulite to high amphibolite facies conditions. Some igneous cryptic chemical variations are preserved in olivine, orthopyroxene, hornblende, plagioclase and magnetite, some leuco-gabbros retain their igneous cumulus plagioclase megacrysts, and rare ultramafics retain their igneous olivine, orthopyroxene, clinopyroxene, and hornblende primocrysts. Chemical migration of elements within and amongst grains during the metamorphism appears to have been small, so that the present minerals have a mixture of both igneous and metamorphic characteristics.